Надежность и долговечность напорных гидротранспортных систем - Махарадзе Л. И. Леон Ильич; Гочиташвили Т. Ш. Теймураз Шалвович; Сулаберидзе Д. Г. Давид Гуриевич; Алехин Л. А. Леван Агасиевич (Москва, Недра, 1984)
Авт. указаны на обороте тит. л.